The forkhead transcription factor Foxo3 negatively regulates natural killer cell function and viral clearance in myocarditis. (9th November 2017) - Loebel, Madlen; Holzhauser, Luise; Hartwig, Jelka A; Shukla, Praphulla C; Savvatis, Konstantinos; Jenke, Alexander; Gast, Martina; Escher, Felicitas; Becker, Sonya C; Bauer, Sandra; Stroux, Andrea; Beling, Antje; et al.
Abstract: Aims: Foxo3 is a transcription factor involved in cell metabolism, survival, and inflammatory disease. However, mechanistic insight in Foxo3 effects is still limited. Here, we investigated the role of Foxo3 on natural killer (NK) cell responses and its effects in viral myocarditis. Methods and results: Effects of Foxo3 on viral load and immune responses were investigated in a model of coxsackie virus B3 myocarditis in wild-type (WT) and Foxo3 deficient mice. Reduced immune cell infiltration, viral titres, and pro-inflammatory cytokines in cardiac tissue were observed in Foxo3 −/− mice 7 days post-infection (p.i.). Viral titres were also attenuated in hearts of Foxo3 −/− mice at Day 3 while interferon-γ (IFNγ) and NKp46 expression were up-regulated suggesting early viral control by enhanced NK cell activity. CD69 expression of NK cells, frequencies of CD11b + CD27 + effector NK cells and cytotoxicity of Foxo3 −/− mice was enhanced compared to WT littermates. Moreover, microRNA-155 expression, essential in NK cell activation, was elevated in Foxo3 −/− NK cells while its inhibition led to diminished IFNγ production. Healthy humans carrying the longevity-associated FOXO3 single nucleotide polymorphism (SNP) rs12212067 exhibited reduced IFNγ and cytotoxic degranulation of NK cells. Viral inflammatory cardiomyopathy (viral CMI) patients with this SNP showed a poorer outcome due to less efficient virus control. Conclusion: Our results implicate Foxo3 in regulating NK cell function and suggest Foxo3 playing an important role in the antiviral innate immunity. Thus, enhanced FOXO3 activity such as in the polymorphism rs12212067 may be protective in chronic inflammation such as cancer and cardiovascular disease but disadvantageous to control acute viral infection.